MERGER OF INDONESIAN ISLAMIC BANKS: BUSINESS COMPETITION LAW AND PROTECTION OF CUSTOMERS RIGHTS - Romlah, Siti; Amin, Muhammad; Hasanah, Nur (Universitas Syiah Kuala, 2024)
The merger of three Islamic banks into BSI has ignited discussions on monopolistic practices and unfair business competition. Some argue that BSI's merger breaches business competition law, specifically Law No. 5 of 1999, due to its control of over 50% of the market share of Islamic commercial banks. However, this argument lacks clarity on the determination of the relevant market, a crucial factor for assessing market dominance and potential monopolistic behavior. This article delves into the BSI merger process, analyzing market share within the defined market as outlined in Law No. 5 of 1999 and its associated regulations. Furthermore, it explores customer protection measures during the merger. The findings indicate that BSI's actions within the relevant market do not exhibit signs of monopolistic practices or unlawful business combinations prohibited by Law No. 5 of 1999. BSI has adhered to all regulatory requirements, ensuring customer protection throughout the merger process.